Proyecto tecnico para la construccion de un sistema de agua potable, alcantarillado sanitario, pluvial y planta de tratamiento de AA.SS. De los sitios parlamento, Sorbona y Valeriano Naula, pertenecientes, a la parroquia Barbones del cantón el guabo Provincia de el Oro - Fajardo Jimenez, Jorge Javier (2015)
The availability of good quality water for human consumption , it is essential for the development of peoples. As well as preserve the health of its inhabitants ; considering that the urbanization of social interest Carrion Square lacks this service are obvious deficiencies in the system of water supply , this has led to a review of the current conditions of the system as its shortcomings and possible solutions. indifference to this reality aggravate the problem of population health therefore study and design are a necessity not made ​​a correct design on the system of potable water, sanitary and storm sewer and its consequences, an epidemiological profile warns prevalent related to the quality of water that would affect the population if the unhealthiness of the area caused epidemic spread of communicable diseases such as diseases : cholera dengue , typhoid , etc.